Exploring Mouth Opening in 3–14-year-Old Children in a Tertiary Care Centre of Nepal - Shah, Priyanka; Khanal, Sanskriti (Nepal Medical College Journal, 2024)
Mouth opening plays a crucial role in our daily lives. Maximum mouth opening is an important parameter in the assessment of several clinical situations and its value is documented to have variations with gender, age and individual’s physical characteristics. This cross-sectional study was carried out to measure the clinical maximum mouth opening in children and its correlation with age, gender, height and weight. A total of 301 children of 3 to 14 years old were included in the study. Data was analyzed using SPSS 16. The mean maximum mouth opening seen in male was 43.17 ± 6.09 mm and in female was 42.55 ± 6.13 mm. Mouth opening differences among different gender was not significant. The mean maximum mouth opening in 3 to 5 years age group was 35.71 ± 4.88 mm, 6 to 8 years age group was 41.71 ± 4.86 mm, 9 to 11 years age group was 44.82 ± 4.61 mm, and 12 to 14 years age group was 47.73 ± 5.84 mm. There was significant difference in the mouth opening of different age groups. There was a positive significant correlation between MMO and weight (Pearson’s correlation coefficient r = 0.592; P < 0.0001) as well as between MMO and height (r = 0.616; P < 0.0001).